Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1600-051x.2009.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation status of the IL8 gene promoter in oral cells of smokers and non‐smokers with chronic periodontitis

Abstract: We conclude that inflammation in the oral mucosa might lead to changes in the DNA methylation status of the IL8 gene in epithelial oral cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 44 publications
7
95
0
1
Order By: Relevance
“…Recent studies showed a higher percentage of interleukin-8 hypomethylation in epithelial cells from individuals with chronic periodontitis and with aggressive periodontitis (Oliveira et al 2009;Andia et al 2010). However, the same was not observed when assessed DNA from gingival tissue cells in chronic periodontitis (Oliveira et al 2009). Zhang et al (2010) showed that hypomethylation in interferon-gamma (IFN-) promoter region is associated with an increase of IFN-␥ expression in chronic periodontitis biopsies.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies showed a higher percentage of interleukin-8 hypomethylation in epithelial cells from individuals with chronic periodontitis and with aggressive periodontitis (Oliveira et al 2009;Andia et al 2010). However, the same was not observed when assessed DNA from gingival tissue cells in chronic periodontitis (Oliveira et al 2009). Zhang et al (2010) showed that hypomethylation in interferon-gamma (IFN-) promoter region is associated with an increase of IFN-␥ expression in chronic periodontitis biopsies.…”
Section: Discussionmentioning
confidence: 96%
“…All rights reserved. doi:10.1016/j.imbio.2011.01.006 the cytokine expression is unregulated, such as chronic gastritis (Bobetsis et al 2007), airway inflammation (Adcock et al 2009), periodontitis (Offenbacher et al 2008;Oliveira et al 2009) and bronchial asthma (Kwon et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine gene expression may be regulated by epigenetic changes (Adcock et al 2009) and these mechanisms have been evaluated in some cytokine genes such as IL-4, IL-6, IFN-␥, IL-10, IL-8, and others (Szalmás et al 2008;Adcock et al 2009;Armenante et al 1999;Kwon et al 2008;Oliveira et al 2009). Evidence suggests that epigenetic events in cytokine genes may be important in understanding the pathogenesis of inflammatory diseases in which 0171-2985/$ -see front matter © 2011 Elsevier GmbH.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have investigated the role of epigenetics in chronic or aggressive periodontitis [36][37][38], and have demonstrated that the expression levels of cytokines and chemokines [39], toll-like receptors [40], protease-activated receptors [41], interleukin-8 [42], and cyclooxygenase-2 [37,38] could be affected by oral bacteria. A recent study documented that the presence of different oral bacteria resulted in a differential methylation profile in gingival epithelia [43], while another article demonstrated hypomethylated oral epithelia in patients with generalized aggressive periodontitis [36].…”
Section: Dna Methylationmentioning
confidence: 99%